2020
DOI: 10.3390/jcm9072217
|View full text |Cite
|
Sign up to set email alerts
|

HLA-Matched Allogeneic iPS Cells-Derived RPE Transplantation for Macular Degeneration

Abstract: Immune attacks are key issues for cell transplantation. To assess the safety and the immune reactions after iPS cells-derived retinal pigment epithelium (iPS-RPE) transplantation, we transplanted HLA homozygote iPS-RPE cells established at an iPS bank in HLA-matched patients with exudative age-related macular degeneration. In addition, local steroids without immunosuppressive medications were administered. We monitored immune rejections by routine ocular examinations as well as by lymphocytes-graft cells immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(115 citation statements)
references
References 32 publications
1
103
0
2
Order By: Relevance
“…Immune rejection occurs after allogeneic transplantation of iPSC-RPEs in vivo, despite the fact that the transplant iPSC-RPEs are capable of inhibiting T-cell activity and the transplantation site, the sub-retinal space, is an environment less prone to inflammation as well as the vitreous [54][55][56]. We also reported that immune rejection occurs in one of five age-related macular degeneration patients after allogeneic transplantation of iPSC-RPEs [10]. In humans, however, we would expect that iPSC-RGCs would be less likely to cause rejection than transplantation of iPSC-RPEs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Immune rejection occurs after allogeneic transplantation of iPSC-RPEs in vivo, despite the fact that the transplant iPSC-RPEs are capable of inhibiting T-cell activity and the transplantation site, the sub-retinal space, is an environment less prone to inflammation as well as the vitreous [54][55][56]. We also reported that immune rejection occurs in one of five age-related macular degeneration patients after allogeneic transplantation of iPSC-RPEs [10]. In humans, however, we would expect that iPSC-RGCs would be less likely to cause rejection than transplantation of iPSC-RPEs.…”
Section: Discussionmentioning
confidence: 68%
“…Retinal pigment epithelial cells (RPEs), which are one of the constituent cells of the retina as well as RGCs, have been reported to possess immune-suppression capacity [ 2 , 3 , 4 , 5 , 6 ]. Stem cell-derived RPE transplantation therapy has already been applied clinically [ 7 , 8 , 9 , 10 ]. On the other hand, to date, no reports have described the immunological characteristics of RGCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an allogeneic cell suspension of iPSC-RPE derived from a super-donor carrying the most common HLA haplotype in Japan, which matched the HLA type of recipients, was transplanted into five patients with AMD without using immunosuppressive medications. Notably, they found that grafted cells stably remained during the 1 year observation period, although mild immune rejections were observed in one patient (Sugita et al, 2020). However, as described above, it remains to be elucidated whether HLA matching is sufficient to prevent long-term immune rejections in humans in other contexts.…”
Section: Hla-matched Allogeneic Ipscsmentioning
confidence: 99%
“…As discussed above, the same group has transplanted cell suspension of iPSC-RPE derived from an HLA-matched superdonor into five patients. The grafted cell location was not sufficiently controlled to access the efficacy of this therapeutic approach, and further optimization of the surgical procedure for the human iPSC-RPE cells transplantation will be necessary in future studies (Sugita et al, 2020).…”
Section: Macular Degenerationmentioning
confidence: 99%
“…Retinal pigment epithelial (RPE) cells located in the posterior segment of the eye are also immune privileged cells and have a T-cell-suppressing effect. However, RPE cells, which are known to be immunogenic cells, have major histocompatibility complex (MHC) expression and experience rejection after RPE cell transplantation [ 4 , 5 , 6 , 7 , 8 ]. In other words, it is considered that RPE cells are highly likely to exhibit immunogenic (immunity promoting) or immunosuppressive effects, two properties of intraocular inflammation.…”
Section: Introductionmentioning
confidence: 99%